3D modelling of thallus topography of Lobaria pulmonaria facilitates understanding of water storage pools. (20th February 2019) - Phinney, Nathan H.
Abstract: Lobaria pulmonaria is a widespread epiphytic foliose lichen that exhibits a prominent reticulum, a structure that has a presumed role in mechanical support and water capture. Using photogrammetry, thallus topography was digitally modelled in three dimensions to calculate 3D surface area (A3D ), which was consistently greater than areas extracted from projected images (A2D ). The A3D :A2D ratio, a proxy for topographic three-dimensionality, was strongly correlated with both specific thallus mass (STM) and external water-holding capacity (WHCexternal ), suggesting that the reticulum in L. pulmonaria extends hydration, photosynthetic activity and growth, following rainfall. Three-dimensionality was more pronounced in larger thalli, which is likely beneficial to liquid water-dependent internal cephalodia that occur more in older thalli and most often within the fovea.